Plant Breeding Techniques in Tissue Culture to Improve the Quality of Orchids - Mukhamad Su'udi; Waki’atil Rosida; El Shania Ravitamala; Arif Mohammad Siddiq; Rendy Setiawan; Dwi Setyati; Asyifa Yasmin Ningrum; Wasiatur Roziqoh (Institut Pertanian Bogor, 2025)
Conventional orchid cultivation is thought to be ineffective and time-consuming. Simple tissue culture procedures are insufficient to increase orchid quality. The need for ongoing development can be met by integrating different plant breeding strategies in orchid tissue culture, such as induction mutation, elicitor addition, and genetic transformation. The purpose of this article was to report on current improvements in the use of plant breeding techniques to orchid tissue culture to increase orchid quality. This article referenced significant scientific publications. Orchid tissue culture using mutation induction is used to develop improved variations. Giving elicitors can cause orchid plants to conserve themselves and become more resistant to diseases. The required transgene can be introduced into the genome of cultivated orchids via Agrobacterium. These advancements have the potential to revolutionize orchid cultivation. Keywords: biotechnology, orchid, tissue culture